NEW MONOGRAPH BY BOHDAN KINDRATYUK ON THE MUSICAL ART OF THE HALYC-VOLYN PRINCIPALITY (Південний архів (історичні науки), 2025)
NEW MONOGRAPH BY BOHDAN KINDRATYUK ON THE MUSICAL ART OF THE HALYC-VOLYN PRINCIPALITY